Can technological innovation, foreign direct investment and natural resources ease some burden for the BRICS economies within current industrial era?. (August 2022) - Gyamfi, Bright Akwasi; Agozie, Divine Q.; Bekun, Festus Victor
Abstract: Economic advancement has tended to affect the processes of industrialization, which has increased the value of exploited natural resources via the application of technology. Intensive use of natural resources via total reserves, technological innovation, foreign direct investment (FDI), and renewable energy can have an impact on the environment. Considering this, the present study investigates the nexus between industrialization, total reserves, inflows of FDI, technical innovation, renewable and natural resources, and CO2 emissions in the case of BRICS. To this end, annual frequency data for BRICS from 1990 to 2019 are employed in panel framework. The study employs a battery of econometric techniques, namely the Augmented Mean Group (AMG), Common Correlated Effects Mean Group (CCEMG), and Driscoll-Kraay estimators to explore the underlined relationship. The cointegration results based on Westerlund, J. (2007) show that there exists a long-run equilibrium relationship between the study outlined variables over the investigated period. From the empirical analysis, technological innovation and renewable energy both reduce CO2 emissions while industrial value-added, natural resources, FDI and total reserves contribute to the degradation of the environment. Additionally, the interaction between industrial value-added and technological innovation also has negative impact on the BRICS countries' environment. Based on these outcomes, the BRICS economies are enjoined to pursue green technology growth without compromise for environmental quality in the bloc. Finally, numerous significant policy ramifications for protecting environmental quality in BRICS economies have been proposed in the concluding section. Highlights: We explore the impacts ICT and industrialization on CO2 emissions in BRICS. We applied a battery of second-generation panel econometrics methods. Natural resources worsens the environmental quality in the investigated bloc. Renewables shows strong evidence to improve the quality of the environment in BRICS.